1981
DOI: 10.1080/03015521.1981.10427819
|View full text |Cite
|
Sign up to set email alerts
|

The acute oral toxicity of the anticoagulant brodifacoum to dogs

Abstract: The oral toxicity of an anticoagulant, brodifacoum, was tested with dogs of mixed breed, age, and sex. In the first trial using 20 dogs, predominantly under 2 years old, an acute oral LDso of 1.09 rng kg-l (95% confidence limits, 0.49-2.42 rng kg-I) was derived. In the second trial with 59 mixed age dogs an acute oral LDso of 3.56 rng kg-I (2.13-6.03 rng kg-I) resulted. No significant differences as a result of age or sex were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 6 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Reports in the U.S. of secondary poisoning to pets from SGARs do not figure in the veterinary literature (Murphy andGerken 1986, Corrigan 2001), yet dogs and cats represent a far more likely scenario in being exposed to poisoned commensal rodents than wildlife. The toxicity of SGARs to dogs has been variously reported, and the most robust study puts brodifacoum as comparable in toxicity (LD 50 of 3.56 mg/kg) to the other SGAR products with regard to canines (Godfrey et al 1981). Diphacinone, a FGA rodenticide which would not be restricted under the EPA's proposal, is as toxic to canines as some SGARs, and cats and dogs are highly susceptible to the effects of the acute rodenticide cholecalciferol, which at 750 ppm is from 15 to 30 times more concentrated than the SGARs (Corrigan 2001).…”
Section: Potential Hazards To Companion Animalsmentioning
confidence: 99%
“…Reports in the U.S. of secondary poisoning to pets from SGARs do not figure in the veterinary literature (Murphy andGerken 1986, Corrigan 2001), yet dogs and cats represent a far more likely scenario in being exposed to poisoned commensal rodents than wildlife. The toxicity of SGARs to dogs has been variously reported, and the most robust study puts brodifacoum as comparable in toxicity (LD 50 of 3.56 mg/kg) to the other SGAR products with regard to canines (Godfrey et al 1981). Diphacinone, a FGA rodenticide which would not be restricted under the EPA's proposal, is as toxic to canines as some SGARs, and cats and dogs are highly susceptible to the effects of the acute rodenticide cholecalciferol, which at 750 ppm is from 15 to 30 times more concentrated than the SGARs (Corrigan 2001).…”
Section: Potential Hazards To Companion Animalsmentioning
confidence: 99%
“…However, because phosphorus is an inhumane poison, the halogenated anticoagulant brodifacoum has been proposed as an alternative (Godfrey & Lyman 1980). Previous trials (Godfrey & Lyman 1980 Godfrey et al 1981a) have shown the effectiveness of brodifacoum against rabbits. Other trials have shown that brodifacoum poses less danger to dogs (Godfrey et al 1981b), and no greater danger to birds, than compound 1080 (Godfrey unpublished data).…”
Section: Introductionmentioning
confidence: 99%